Development of a Functional Observational Battery in the Minipig for Regulatory Neurotoxicity Assessments. (March 2017) - Zhong, Miao; Shoemake, Catherine; Fuller, Amber; White, David; Hanks, Chris; Brocksmith, Derek; Liu, Jason; Gad, Shayne; Bouchard, Guy; Stricker-Krongrad, Alain
A functional observational battery (FOB) is recommended as the first-tier neurotoxicity screening in the preclinical safety pharmacology testing guidelines. Minipigs have increasingly been used in regulatory toxicology studies; however, no current FOB protocol is available for neurotoxicity testing in these species. Hence, a minipig FOB instrument was developed. A complete crossover study with Sinclair minipigs was performed to evaluate physiologic, neurologic, and behavioral effects of amphetamine, ketamine, and diazepam. The treated minipigs were first observed in their home cage, were video-recorded for 10 minutes in an open field, and then went through a complete neurologic examination. Both ketamine and diazepam were shown to reduce the freezing and behavior shifts of treated minipigs, while increasing their exploratory behaviors. Both drugs also caused muscular and gait impairment. The effects of ketamine and diazepam were consistent with their roles as central nervous system (CNS) suppressants. Unique effects were also observed with ketamine and diazepam treatments, which may reflect their unique mechanisms of action. Consistent with its role as a CNS stimulant, amphetamine caused the treated minipigs to be hyperactive and to display increased freezing and behavior shifts and reduced exploring activities. These effects of amphetamine were opposite to those observed with ketamine and diazepam. Amphetamine also increased locomotion in the treated minipigs. The present effects of amphetamine, ketamine, and diazepam are in agreement with observations by others. In conclusion, the minipig is a suitable species for FOB evaluation of pharmaceuticals in preclinical safety pharmacology testing.